Turnall holdings online helpdesk and support system - Chibagidi, Prince (Midlands State University, 2018)
The purpose of the study was to develop an online mobile application to perform the task of reporting IT related faults and issues that arise at Turnall Holdings so as to capture and store all these problems for future reference easily. The objectives of the system were to remove the use of manual paper as log sheets, which consumed a lot of resources and money. The system was to create a quick reaction on the IT stuff by showing dates and times of the report of a fault and the attendance to it. The IT manager of Turnall Holdings also wanted a way to measure the work done by the IT staff on a daily or weekly basis to see how they were responding to user problems and solving them. The system was to make users feel comfortable to report their faults in the way they wanted and not have to call through the phone for IT who may not be around the office at that time. Using the various data gathering methodologies available which include interviews, questionnaires and observations, the student gained more insight on how the system works and what new things he can include in the development of the new system. The student then solved the problems by developing an android mobile application that will be used by Turnall holdings to report and document faults while providing a good reporting structure as well. The system was implemented using the android operating platform on mobile devices like smart phones and tablets so as to allow communication between users and IT. Each user has his/her own mobile device that they use to report the faults and the IT personnel have their own devices they use to attend to the faults. In future, the system can be enhanced such that they link with the profiles of each user on the computer such that when such cases like when the user is locked out the system automatically sends the report.